Gwarancje ubezpieczeniowe jako instrument ochrony interesów jednostek samorządu terytorialnego - Różycki, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Wrong performance of contract is a risk connected with every contract. Local government is cooperating with many entities so it is exposed to this risk as well. Protect against this risk is one of the tool of risk management. Because of tasks and aims of local government proper protection against that kind of risk seems to be necessary and obvious. Public procurement creates of using different kinds of protection. There are for example performance bonds and bid (tender) bonds. These kinds of bonds can be very useful for local governments as a tool of protection their activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 578-585